Antioxidant Properties of Some new Synthesized Shciff Bases Derived from 1, 2, 4- Triazole Ring (Journal of the College of Basic Education, 2022)
Some Schiff' bases were derived from triazole ring which have the name ( 4-1,2,4-triazole-2-yl-diazenyl )-1-(substituted benzylideneamino) benzene . They were prepared through the reaction of N-amino triazole, a mixture of ( HCl and NaNO2 ) and aniline . The product was reacted with series aromatic aldehydes to form Schiff' bases, the final products were identified by the available spectroscopic methods and tested their activity as antioxidants by using some chemical indicators.